About the Calculation Method of the Coefficient that Shows Significance Extent of Geometric Characteristics in Determination of Racial and Ethnic Identity of Human - Kazimov, Tofig; Mahmudova, Shafagat (Review of Computer Engineering Research, 2016)
In the article, a new algorithm for finding coefficients that determine significance extent of the values of geometric characteristics that are used for determination of racial and ethnic identity of human is proposed. It is explained that the calculation of coefficients which determine the importance extent of the values of geometric characteristics is important in several respects. The determination of coefficients that indicate the importance extent of geometric characteristics causes reduction in numbers of values of geometric characteristics that don’t have particular importance and in time that is spent for the identification and improvement of identification quality.